Memahami Akhlaq di era society 5.0: Pengaruh influencer terhadap generasi penerus bangsa - Albukhari, Shofia (Maliki Interdisciplinary Journal, 2024)
The influence of influencers in shaping the akhlaq or morality of the nation’s next generation in the era of society 5.0. The era of society 5.0 is characterized by rapid technological development, where social media and influencers have a significant role in people’s daily lives, especially the millennial generation. Independent surveys show that influencers have an important and influential role, especially for teenagers. The influence of influencers and social media has also been proven to influence consumptive behavior in the digital era. Therefore, it is important to understand how the influence of influencers can impact the akhlaq of the nation’s next generation. Akhlaq education in the millennial generation aims to form a strong and responsible character in using social media and digital technology. In welcoming the era of society 5.0, families also have an important role in shaping the akhlaq of the nation’s next generation. Strengthening the family in the perspective of Islamic psychology can help overcome the challenges faced in this digital era, by understanding the influence of influencers and social media, as well as the role of akhlaq education and family, we can take the right steps to form the next generation of nations that have good akhlaq in the era of society 5.0